Reading the Brontë body : disease, desire, and the constraints of culture - Torgerson, Beth E. (Beth Ellen) (Palgrave Macmillan, 2005)
Anne, Emily, and Charlotte Brontë's literary representations of illness and disease reflect the major role illness played in the lives of the Victorians and its frequent reoccurrence within the Brontës' personal lives. An in-depth analysis of the history of nineteenth-century medicine provides the cultural context for these representations, giving modern readers a sense of how health, illness, and the body were understood in Victorian England. Together, medical anthropology and the history of medicine offer a useful lens with which to understand Victorian texts. Reading the Brontë Body is the first scholarly attempt to provide both the theoretical framework and historical background to make such a literary analysis of the Brontë novels possible, while exploring how these representations of disease and illness work within a larger cultural framework.